An institutional approach to the development of business angel networks in Latin American emerging countries. Issue 6 (10th June 2021) - Martins, Izaias; Romaní, Gianni; Atienza, Miguel
Abstract : Purpose: The purpose of the paper is to analyze the development of business angel networks (BANs) in emerging countries such as Chile and Colombia to understand how institutions affect their development. Design/methodology/approach: This is a qualitative, exploratory, and descriptive study based on a comparative analysis between countries, with the BANs in Chile and Colombia as the unit of observation. The comparative analysis was made in relation with the creation, operation and sustainability of the BANs. The study interviews the partners/managers of the active networks in each of the countries, as well as key informants, totalling 12 interviews. Findings: BAN activity in Chile and Colombia is quite recent, and the countries are on a similar level of development. However, in the long term, depending on how the cultural aspects evolve in both countries and the interest that the State may have in developing business angel activity, the results could be indeed different. Originality/value: Business angel activity in Latin America is quite recent; nevertheless, this activity is increasing in the region. In that sense, this comparative analysis between Colombia and Chile contributes to a better understanding of business angel markets in Latin America and also to obtain better insights into the core challenges that these markets face in emerging countries due to the existence of institutional voids. This paper is a contribution for further knowledge of BANs in emerging countries' economies from an institutional perspective.